Management strategy of a carotid-esophageal fistula with a right common carotid artery pseudoaneurysm due to chicken bone ingestion: A case report and literature review - Xu, Dongming; Qian, Haichao; Lian, Lishan; Xie, Miaorong; Zhang, Hanyu (Frontiers in Surgery, 2023)
Common carotid artery (CCA) pseudoaneurysm is a rare clinical disorder. CCA pseudoaneurysm that occurs with a carotid-esophageal fistula and causes massive upper gastrointestinal bleeding is especially uncommon but can be life-threatening. Accurate diagnosis and prompt managements are essential to save lives. Here, we report a case of a 58-year-old female who presented with dysphagia and throat pain after accidental ingestion of a chicken bone. The patient presented with active upper gastrointestinal bleeding which quickly developed into hemorrhage shock. Imaging studies confirmed a diagnosis of right CCA pseudoaneurysm and carotid-esophageal fistula. The patient had a satisfactory recovery after a right CCA balloon occlusion, right CCA pseudoaneurysm excision, and right CCA and esophageal repairs. We present and discuss this case here to remind physicians to rule out rare causes of upper gastrointestinal bleeding. A multidisciplinary approach is commonly required to achieve satisfactory outcomes in these cases.